Non-conventional methods for energy extraction from high voltage transmission lines - Nicolae, Dan Valentin (My University, 2013)
A comprehensive study upon "Non-conventional methods for energy extraction from the high voltage transmission lines" was addressed in this thesis. As defined in this study, a non-conventional method to extract energy is one that does not touch the conductors of the line. The theoretical framework which originated in the Maxwell's equations was presented as a base for discussion of all the methods and the conditions for the extraction to be possible. This study presents various methods such as capacitive and inductive to extract energy from high voltage alternating current transmission lines (HVAC). Although in theory, for high voltage direct current transmission lines (HVDC), the conditions for extraction are not matched, there remain some methods that could still attract interest. The centre point of this thesis is the new power application of the Rogowski coil. This method is analysed in full extent starting from theoretical modelling, computer simulations, design of the actual Rogowski coil and power electronics associated with it, and experimental results on a reduced scale model. In doing this, strong mathematical tools and computer software such as Matlab 6, Quick Field and MathCAD were used. At the end of this thesis, some conclusions are presented together with new ideas for further research in the field.
Thesis (D. Tech. Electrical engineering) --Vaal University of Technology
Keywords: Energy extraction; High voltage transmission lines; Rogowski coil; 621.31922; Electric power transmission; High voltages.